Method for characterizing surface charge of inorganic salt based on electrochemical means

By measuring its zero charge potential in the saturated solution of the inorganic salt, the problem of difficulty in accurately characterizing the surface charge of the inorganic salt in the prior art is solved, and the effect of accurately characterizing the surface charge of the inorganic salt is achieved without grinding.

CN119715708AActive Publication Date: 2025-03-28TIANJIN UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411887704.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to accurately characterize the surface charges of most inorganic salts, especially those with large particle size and poor dispersion. Grinding will damage the crystal structure and cause data distortion.

Method used

Using an electrochemical method, the inorganic salt surface charge was characterized by flaking the inorganic salt into an electrode sheet and measuring the zero charge potential (PZC) in its saturated solution. This method does not require grinding, ensuring the integrity of the inorganic salt crystals.

Benefits of technology

It can accurately characterize the charge conditions of the surface of inorganic salts, ensure the authenticity and accuracy of the data, and judge its adsorption effect on anions or cations based on the positive and negative of the zero-charge potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119715708A_ABST
    Figure CN119715708A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic salt surface charge characterization, and relates to a method for characterizing inorganic salt surface charges based on an electrochemical means, which comprises the following steps of: processing inorganic salt into an electrode plate based on the electrochemical means, and measuring zero charge potential of the inorganic salt in a saturated solution of the electrode plate by taking the saturated solution of the electrode plate as electrolyte. The method does not need to grind the inorganic salt, ensures the completeness of the crystal face of the inorganic salt crystal, and can accurately characterize the charge condition of the inorganic salt surface in the saturated solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic salt surface charge characterization, and relates to a method for characterizing the surface charge of an inorganic salt based on electrochemical means. Background Art

[0002] Characterizing the surface charge of inorganic salts has important theoretical and practical significance. It not only helps to understand the basic physical and chemical properties of materials, but also plays a key role in multiple application fields. Understanding the surface charge state of inorganic salt crystals is crucial for studying their surface chemical reactivity, adsorption behavior, and interfacial phenomena. Surface charge affects processes such as ion exchange, solubility, and precipitation. The surface charge distribution can reveal the kinetics and thermodynamics of crystal growth and help explain the changes in crystal morphology under different conditions. The flotation method in mineral processing utilizes the selective attachment between mineral particles and bubbles, and the surface charge is one of the important factors that determine the flotation effect. Understanding the surface charge of fertilizer particles helps to develop more efficient slow-release fertilizers, reduce nutrient loss, and improve crop absorption. Characterizing the surface charge of inorganic salts provides a bridge for understanding the microstructure and macroscopic behavior of materials, and promotes extensive progress from basic research to practical applications. By deeply exploring the mechanism of surface charge, it is not only possible to optimize existing materials and technologies, but also to inspire the research and development of new functional materials and promote innovation and development in multiple fields.

[0003] At present, the commonly used methods for characterizing the surface charge of inorganic salts include Zeta potential measurement, Kelvin probe force microscopy, rheology and dynamic light scattering. However, these methods have very high requirements on the particle size of inorganic salts, requiring the inorganic salt particles to reach the micrometer level or even the nanometer level, and require excellent dispersibility. In practical life, the inorganic salt particles are large in size and poor in dispersibility. In order to measure their surface charge, physical grinding is required, but grinding will destroy the crystal structure of the inorganic salt, resulting in distortion of the surface charge data, which cannot accurately and truly reflect the actual crystal surface charge situation.

[0004] The Zeta potential measurement method characterizes the surface potential of inorganic salts. It requires that the salt particles have a particle size of micrometers, can exist stably in the dispersant, and have good dispersibility, which restricts the characterization of inorganic salts by this method. The commonly used dispersants for the Zeta potential measurement method are water and ethanol. Since inorganic salts are easily soluble in water, water cannot be used as a dispersant for inorganic salts. For some inorganic salts containing hydrates, such as carnallite (KCl·MgCl2·6H2O) and potassium magnesium alum (KCl·MgSO4·3H2O), they will also decompose in ethanol, so inorganic salts can only be dispersed in the corresponding saturated solution. However, the Zeta potential measurement method has some limitations on the conductivity of the dispersant. The excessive conductivity of the saturated solution of the inorganic salt usually exceeds the conductivity range of the Zeta potential measuring instrument. In summary, even if the inorganic salt particle size is made to meet the standard by means of grinding, due to the problem of dispersant selectivity, the Zeta potential measurement method is difficult to meet the characterization needs of the surface potential of most inorganic salts.

[0005] Kelvin probe force microscopy is a technology based on atomic force microscopy (AFM) that can measure surface potential at the nanoscale, thereby reflecting the surface charge distribution. Inorganic salts are characterized by this method, and the particle size needs to be controlled to the nanoscale through physical grinding and other means. Inorganic salts exist in the form of crystals. Grinding will destroy the crystal structure and change the exposed crystal surface, thereby affecting the charge on the surface of the inorganic salt. Therefore, the surface charge data measured by this method is distorted and cannot strictly reflect the charge on the surface of the inorganic salt.

[0006] Therefore, a method is needed to accurately characterize the surface charge of inorganic salts. Summary of the invention

[0007] Potential of Zero Charge (PZC) is the potential value when the charge on the electrode surface is zero. In the field of electrochemistry, PZC is an important parameter to describe the properties of the electrode-electrolyte interface. By measuring PZC, we can understand the charge state and charge properties of the electrode surface at different potentials. When PZC<0, it means that the electrode surface potential is reduced and the surface charge reaches zero, indicating that there is a positive charge on the electrode surface; when PZC>0, it means that the electrode surface potential is increased and the surface charge reaches zero, indicating that there is a negative charge on the electrode surface. Using this principle, using inorganic salts as electrodes, the surface charge of inorganic salts can be determined by characterizing PZC.

[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for characterizing the surface charge of an inorganic salt based on electrochemical means. Based on electrochemical means, an inorganic salt is processed into an electrode sheet, and its saturated solution is used as an electrolyte to measure the zero charge potential of the inorganic salt in its saturated solution. The method does not require grinding of the inorganic salt, ensures the integrity of the crystal face of the inorganic salt crystal, and can accurately characterize the charge of the inorganic salt surface in its saturated solution.

[0009] The technical solution adopted by the present invention to solve the technical problem is:

[0010] A method for characterizing the surface charge of inorganic salts based on electrochemical means, the steps are as follows:

[0011] (1) Preparation of salt electrode sheet:

[0012] The inorganic salt to be tested is pressed into a salt electrode sheet, the pressing pressure is controlled at 12-14 MPa, and the pressing thickness is controlled at 0.2-1.5 mm;

[0013] (2) performing electrochemical characterization on the salt electrode sheet, including:

[0014] 1) Build the device:

[0015] Using an electrochemical workstation, install the prepared salt electrode sheet on the working electrode, select the counter electrode and reference electrode, and use a saturated solution of the inorganic salt to be tested at the corresponding temperature as the electrolyte;

[0016] 2) Set the electrochemical workstation parameters:

[0017] Select the step potential electrochemical impedance spectroscopy (Mott-schottky)-SPEIS) function of the electrochemical workstation. The scanning voltage range can be appropriately adjusted according to different types of salt electrodes and set to -1.0~1.0V. The more scanning steps are set, the more accurate the final result will be, but the test time will also be longer. Set the step length to 0.02~0.05V. The frequency must not be higher than 200mHz and is set to 10~50mHz. The electrochemical workstation will test the capacitance value between the surface of the salt electrode and the reference electrode at different potentials, and finally obtain a curve of the capacitance value of the salt electrode changing with the potential.

[0018] 3) Data processing:

[0019] In the curve of the capacitance value of the salt electrode changing with the potential, the potential corresponding to the minimum capacitance value is the zero charge potential (PZC). In order to more clearly judge the PZC, the data is normalized. The capacitance values ​​under different potentials are compared with the minimum capacitance value, and the obtained ratio is plotted to obtain a normalized capacitance curve. The potential value corresponding to the lowest point of capacitance is the zero charge potential (PZC).

[0020] The tableting pressure is controlled at 12-14 MPa. If the tableting pressure is too low, the mechanical strength of the salt electrode sheet will not meet the standard, and it will easily disperse in the electrolyte solution during the measurement process, or even fail to form. If the tableting pressure is too high, it will easily damage the mold and equipment, and the salt tablet will be difficult to remove from the mold, and it will be difficult to obtain a flat and intact salt electrode sheet.

[0021] The thickness of the pressed sheet is controlled at 0.2-1.5 mm. If the thickness of the pressed sheet is too small, the mechanical strength of the salt electrode sheet will not meet the standard, and it will be easy to bend and break in the electrolyte solution during the measurement process; if the thickness of the pressed sheet is too large, it will not be easy to be fixed by the clamp of the working electrode, and the resistance of the salt electrode sheet will increase, which is not conducive to electrochemical measurement.

[0022] Furthermore, the inorganic salt is an anhydrous salt or a hydrated salt. For anhydrous salts that do not contain water of crystallization, the salt electrode sheets are directly pressed into tablets using a tablet press. For inorganic salts (hydrated salts) that contain a certain number of water of crystallization molecules, a layer of metal mesh is placed at the bottom of the tablet pressing mold, and the pressed salt sheets are loaded onto the metal mesh, which can effectively prevent the salt electrode sheets from breaking and dispersing during the measurement process, thereby preparing salt electrode sheets.

[0023] Furthermore, the metal mesh is a copper mesh, a platinum mesh or a gold mesh.

[0024] Furthermore, in step (1), for the salt electrode sheet prepared from hydrated salt, when assembling the working electrode, the side not loaded with the metal mesh faces the counter electrode, and the side loaded with the metal mesh is supported by an inert electrode sheet and installed on the working electrode.

[0025] Furthermore, the counter electrode is an inert electrode, and the inert electrode is a carbon fiber plate or a platinum sheet.

[0026] Furthermore, the reference electrode is any one of a saturated calomel electrode, a silver / silver chloride electrode, and a double salt bridge reference electrode.

[0027] The advantages and positive effects of the present invention are:

[0028] The present invention adopts a tablet pressing method to prepare an inorganic salt electrode, and measures the zero charge potential of the salt electrode sheet by a capacitive potentiometer to characterize the surface charge of the inorganic salt. This method does not require grinding of the inorganic salt, thereby ensuring the integrity of the crystal face of the inorganic salt crystal, and can accurately characterize the charge of the inorganic salt surface in its saturated solution. The adsorption effect of the inorganic salt on anions or cations can be determined based on the positive or negative value of the zero charge potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a photograph of a sodium chloride electrode sheet;

[0030] Figure 2 It is the normalized capacitance curve of sodium chloride in saturated solution at 25℃;

[0031] Figure 3 It is the normalized capacitance curve of potassium salt magnesium sulfate in saturated solution at 25℃;

[0032] Figure 4 This is the normalized capacitance curve of carnallite in a saturated solution at 25°C. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0034] Example 1

[0035] A method for characterizing the surface charge of inorganic salts based on electrochemical means, the steps are as follows:

[0036] Sodium chloride is directly pressed into salt electrode sheets by a tablet press. The tableting pressure is 14 MPa and the tablet thickness is 1.2 mm. The sodium chloride electrode sheets are as follows: Figure 1 shown.

[0037] The surface charge of sodium chloride in its saturated solution at 25°C was characterized using an electrochemical workstation. The prepared sodium chloride electrode was mounted on the working electrode, a saturated calomel electrode was selected as the reference electrode, a carbon fiber plate was selected as the counter electrode, and a saturated sodium chloride solution at 25°C was selected as the electrolyte.

[0038] Select the step potential electrochemical impedance spectroscopy function of the electrochemical workstation, set the voltage range to 0-0.5V, the voltage step to 0.05V, and the frequency to 50mHz. The normalized capacitance curve of the sodium chloride electrode in a saturated solution at 25℃ is as follows Figure 2 shown.

[0039] The zero charge potential of sodium chloride in a saturated solution at 25°C is 0.2V, and PZC>0, indicating that the surface potential of sodium chloride in a saturated solution at 25°C is negative. Therefore, it can be explained that the surface of sodium chloride crystals in a saturated solution of sodium chloride at 25°C has an electrostatic adsorption effect on sodium ions (cations).

[0040] Example 2

[0041] A method for characterizing the surface charge of inorganic salts based on electrochemical means, the steps are as follows:

[0042] Potassium magnesium alum (KCl·MgSO4·3H2O) is pressed into tablets by a tablet press, the tableting pressure is 14MPa, and the tablet thickness is 1.0mm; a layer of copper mesh is placed at the bottom of the tableting mold, and the pressed salt sheet is loaded on the copper mesh to prepare potassium magnesium alum electrode sheets.

[0043] The surface charge of kainite (KCl·MgSO4·3H2O) in its saturated solution at 25℃ was characterized using an electrochemical workstation. The side of the kainite electrode sheet without copper mesh was facing the counter electrode, and the side with copper mesh was supported by a carbon fiber plate and installed on the working electrode. A saturated calomel electrode was selected as the reference electrode, the carbon fiber plate as the counter electrode, and a saturated solution of kainite at 25℃ was selected as the electrolyte.

[0044] Select the step potential electrochemical impedance spectroscopy function of the electrochemical workstation, set the voltage range to -0.8~0.8V, the voltage step size to 0.05V, and the frequency to 50mHz. The normalized capacitance curve of the potassium salt magnesium alum electrode in a saturated solution at 25℃ is as follows Figure 3 shown.

[0045] The zero charge potential of kainite in a saturated solution at 25°C is -0.65V, and PZC < 0, indicating that the surface potential of kainite in a saturated solution at 25°C is positive. Therefore, it can be explained that the surface of kainite crystals in a saturated solution of kainite at 25°C has an electrostatic adsorption effect on anions.

[0046] Example 3

[0047] A method for characterizing the surface charge of inorganic salts based on electrochemical means, the steps are as follows:

[0048] Carnallite (KCl·MgCl2·6H2O) is pressed into tablets by a tablet press, the tablet pressure is 12MPa, and the tablet thickness is 1.0mm; a layer of platinum mesh is placed at the bottom of the tablet pressing mold, and the pressed salt sheet is loaded on the platinum mesh to prepare a carnallite electrode sheet.

[0049] The surface charge of carnallite (KCl·MgCl2·6H2O) in its saturated solution at 25℃ was characterized using an electrochemical workstation. The side of the carnallite electrode that was not loaded with the platinum mesh was facing the counter electrode, and the side loaded with the platinum mesh was supported by a carbon fiber plate and installed on the working electrode. A saturated calomel electrode was selected as the reference electrode, the carbon fiber plate as the counter electrode, and a saturated solution of carnallite at 25℃ as the electrolyte.

[0050] Select the step potential electrochemical impedance spectroscopy function of the electrochemical workstation, set the voltage range to -0.8~0.8V, the voltage step size to 0.05V, and the frequency to 30mHz. The normalized capacitance curve of the carnallite electrode in a saturated solution at 25℃ is as follows Figure 4 shown.

[0051] The zero charge potential of carnallites in a saturated solution at 25°C is -0.55 V, and PZC < 0, indicating that the surface potential of carnallites in a saturated solution at 25°C is positive. Therefore, it can be shown that the surface of carnallites in a saturated solution of carnallites at 25°C has an electrostatic adsorption effect on anions.

[0052] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. A method for characterizing the surface charge of an inorganic salt based on electrochemical means, characterized in that: Here are the steps: (1) Preparation of salt electrode sheet: The inorganic salt to be tested is pressed into a salt electrode sheet, the pressing pressure is controlled at 12-14 MPa, and the pressing thickness is controlled at 0.2-1.5 mm; (2) performing electrochemical characterization on the salt electrode sheet, including: 1) Build the device: Using an electrochemical workstation, install the prepared salt electrode sheet on the working electrode, select the counter electrode and reference electrode, and use a saturated solution of the inorganic salt to be tested at the corresponding temperature as the electrolyte; 2) Set the electrochemical workstation parameters: Select the step potential electrochemical impedance spectroscopy function of the electrochemical workstation, the scanning voltage range is -1.0~1.0V, the step size is set to 0.02~0.05V, and the frequency is set to 10~50mHz. The electrochemical workstation tests the capacitance value between the surface of the salt electrode and the reference electrode at different potentials, and finally obtains the curve of the capacitance value of the salt electrode changing with the potential; 3) Data processing: In the curve of the capacitance value of the salt electrode sheet changing with the electric potential, the electric potential corresponding to the minimum capacitance value is the zero charge potential. The capacitance value is normalized, and the capacitance values ​​under different electric potentials are compared with the minimum capacitance value. The obtained ratio is plotted to obtain a normalized capacitance curve. The electric potential value corresponding to the lowest point of the capacitance is the zero charge potential.

2. The method according to claim 1, characterized in that The inorganic salt is an anhydrous salt or a hydrated salt. For the anhydrous salt, the salt electrode sheet is directly pressed by a tablet press.

3. The method according to claim 2, characterized in that For hydrated salt, a layer of metal mesh is placed at the bottom of the tablet pressing mold, and the pressed salt tablets are loaded on the metal mesh to prepare salt electrode sheets.

4. The method according to claim 3, characterized in that The metal mesh is a copper mesh, a platinum mesh or a gold mesh.

5. The method according to claim 3, characterized in that: In step (1), for the salt electrode sheet prepared from hydrated salt, when assembling the working electrode, the side not loaded with the metal mesh faces the counter electrode, and the side loaded with the metal mesh is supported by an inert electrode sheet and installed on the working electrode.

6. The method according to claim 1, characterized in that The counter electrode is an inert electrode.

7. The method according to claim 6, characterized in that The inert electrode is a carbon fiber plate or a platinum sheet.

8. The method according to claim 1, characterized in that: The reference electrode is any one of a saturated calomel electrode, a silver / silver chloride electrode, and a double salt bridge reference electrode.

Citation Information

Patent Citations

  • Device and method for controlling surface potential

    CN106055016A

  • Ag / SiC electrode, preparation method thereof and application of Ag / SiC electrode in styrene epoxidation

    CN117248235A

  • Efficient stripping method of MXene material prepared by molten salt method

    CN118561281A

  • a method of demonstrating the self-isolation of a metal and the splitting of its surface charge

    RU2015138795A

  • Apparatus and method for measuring charge density distribution

    US20120323513A1